The World of Wetiko: An Investigation - vaughan, rachael (Cosmos and History: The Journal of Natural and Social Philosophy, 2022)
This paper explores the Algonquin concept of wetiko, or windigo—a ruthless cannibal spirit—to explain the state of America today. Native American scholars such as Jack Forbes and Basil Johnston suggest wetikos really exist, and that their insatiable hunger and psychopathic lack of regard for others is at the root of globalization, neo-liberal economics, the destruction of the environment, and the widescale oppression of the world’s people. This paper investigates the relationship between modernism and wetiko, and proposes an origin to the wetiko mindset, asking whether it is archetypal, and therefore potentially present in all of us, though more actualized in some. Finally it asks how indigenous societies have historically guarded against wetiko and how we can learn from them to resist wetikos now, since if we fail to confront them, they will eat us all alive.